In Vivo production of nosema bombycisSpores and their efficacies against diamondback moth and beet armyworm larvae in laboratory conditions - Syarafina Ramli,; Zainal-Abidin .B.A.H,; Idris .A.B, (Universiti Kebangsaan Malaysia, 2011)
Diamondback moth (DBM), Plutella xylostella and beet armyworm (BAW), Spodoptera exigua are major insect pests of crucifer crops found worldwide. Since these pests are highly resistant to many chemical insecticides, using biological control agent(s) or biopesticides might be a good choice to overcome this problem. Nosema bombycis is a microsporidial pathogen with the potential to control insect pests. This study was aimed at producing N. bombycis spores in vivo and to test their efficacies against DBM and BAW in laboratory conditions. Production of this pathogen was carried out by feeding both DBM and BAW larval instars with artificial diet inoculated with viable spores of N. bombycis. Spore concentrations in the larvae were determined and accumulated. If a concentration of 1.56×108 spores/mL was obtained, the production was continued. For laboratory efficacy tests, artificial diets with different spore concentrations namely 1×104, 1×105 and 1×106 spores/μL were fed to different larval instar. Mortality rates were analysed using the Two-way ANOVA test. For both DBM and BAW, third instar showed the highest mean mortality rates and the mortality in each instars were significantly different (P<0.05). The concentration 1×106 spores/μL caused the highest mean mortality rates and each concentration resulted in significantly different mortality (P<0.05). However, there was no interaction between both factors, where a combination of spore concentrations and instars did not show any significant differences (P>0.05). These results indicated that third instar larvae for both species and 1×106 spores/μL treatments demonstrated the highest efficacy rates